Assessing the Enabling Environment Towards Safely Managed Onsite Sanitation (SMOSS) in Kenya: A Case of Nakuru County - Kiogora, Dominic; Riungu, Joy Nyawira (Meru Universty of Science and Technology International Conference (MUSTIC), 2025)
Kenya, struggling to achieve safely managed sanitation. Less than 10% of the population is connected to the sewer. To this end, Kenyan government has reviewed it targets for sanitation provision strategy to have 60% of its population served by onsite sanitation and only 40% by centralized sewer. Here we sought to assess the enabling environment for scaling up safely managed sanitation in Kenya. Six counties were identified vis Kisumu, Malindi, Samburu, Nakuru, Turkana and Garissa. Key informant interviews (KII) and focus group discussions (FGD) were conducted and data arranged in themes, relevant to enabling environment in onsite sanitation in Kenya. Nakuru has had a long history of leading towards safely managed sanitation being among the very first to adopt the reuse options. Firstly, there is a very strong political goodwill as well as capacity at the Nakuru Municipality management in matters relating to sanitation. Training on City wide inclusive sanitation (CWIS) have been undertaken by persons in the county. There is a very vibrant stakeholder engagement and regular scheduled meetings. The water utility in Nakuru (NAWASCO) has set up a section purely for onsite sanitation. In addition, there in a subsidiary company - NAWASCOAL)- that focuses on reuse. The private sector in well-coordinated and organized. The manual pit-emptiers have been formalized and registered. Artisans have training on onsite technologies. Replicating and adopting the sanitation strategies from Nakuru county in other counties would greatly accelerate on site sanitation as as one of the major drivers to CWIS in Kenya.